SIDS–CDF Hypothesis Revisited: Cause vs. Contributing Factors - Siren, Pontus M. A. (Frontiers in Neurology, 2017)
The sudden infant death syndrome (SIDS)–critical diaphragm failure (CDF) hypothesis was first published by Siren and Siren in 2011 (1). Since its publication, the hypothesis has continued to generate interest and several colleagues have contributed perspectives and insights to it (2–5). The basic premise of the hypothesis is that the diaphragm is a vital organ that must continuously generate adequate force to maintain ventilation, and that CDF is a terminal event and the cause of death in SIDS. I have argued in two follow-up articles that all SIDS factors either increase the workload of the respiratory muscles, the diaphragm being the primary muscle affected, or reduce its force generating capacity (6, 7). The SIDS–CDF hypothesis posits that SIDS has many contributing factors but only one cause, namely, the failure of the vital respiratory pump. There are several known SIDS factors, such as the prone sleeping position, non-lethal infections, deep sleep, gestational prematurity, low birth weight, cigarette smoke, male gender, and altitude, but of these, some such as the prone sleeping position more significantly both impact diaphragm function and correlate with SIDS. However, SIDS cases are multifactorial and as such can be caused by different combinations of factors. An infection combined with a prone sleeping position and elevated room temperature could lead to SIDS, whereas in other circumstances, low birth weight, cigarette smoke, prone sleeping position, and altitude could result in CDF and SIDS. The SIDS–CDF hypothesis also posits that SIDS does not have a congenital or genetic origin, and that efforts to identify significant genetic anomalies in SIDS victims are unlikely to be successful (8–11).